Mortality of working-age physicians compared to other high-skilled occupations in Austria from 1998 to 2020 - Zimmermann, Claudia; Waldhoer, Thomas; Schernhammer, Eva; Strohmaier, Susanne (Scandinavian Journal of Work, Environment & Health, 2024)
' ' OBJECTIVES ': 'Physicians have been shown to have lower mortality compared to the general population, particularly regarding lifestyle-associated causes of death. Prior literature is divided on whether this is due to higher socioeconomic position (SEP), healthier lifestyle, or other specific occupational characteristics. This study analyzed the mortality of Austrian physicians compared to the general population and other (health) professionals with a similar SEP, and investigated patterns of lifestyle-associated mortality among physicians. ' ' METHODS ': 'Data from professional associations and cause-of-death statistics were collated to determine causes of death for all occupational groups. Gender-specific age-standardized mortality rates (ASMR) and standardized rate ratios (SRR) were calculated to compare main causes of death [cancer, cardiovascular disease (CVD), external causes] among physicians to other (health) professionals and the general population. Standardized mortality ratios (SMR) were calculated for more detailed causes of death in physicians compared to the general population. ' ' RESULTS ': 'Physicians had lower all-cause mortality than the general population [SRR 0.45, 95% confidence interval (CI) 0.41–0.49 for males and SRR 0.60, 95% CI 0.54–0.66 for females] and health professionals (SRR 0.72, 95% CI 0.60–0.88 for males and SRR 0.77, 95% CI 0.63–0.93 for females), mostly due to low CVD and cancer mortality. SMR for detailed causes of death among physicians exhibited a pattern of particularly low mortality in lifestyle-associated causes of death and an increased SMR for suicide among female physicians (SMR 1.58, 95% CI 1.22–2.02). ' ' CONCLUSIONS ': 'This study confirmed lower mortality among physicians compared to the general population and compared to other (health) professionals. Low physician mortality can be primarily explained by lifestyle-associated causes of death.
Keywords: Austria; cancer; cause-specific mortality; CVD; female; health profession; high-skilled occupation; lifestyle; mortality; physician; professional; registry study; standardized mortality ratio; standardized rate ratio; suicide